2021
DOI: 10.1021/acs.cgd.0c01476
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Polymorphic Sulfathiazole Controlled by Femtosecond Laser-Induced Cavitation Bubbles

Abstract: Crystals have been widely used in the pharmaceutical industry, structural elucidation, and other biomedical fields. Different polymorphs of one compound possess distinct physical and chemical properties. Some polymorphs are more favorable in applications such as drug delivery and structural characterization. However, owing to the complex mechanisms of the crystallization process, controlling the crystallization result is still difficult. In this study, we found that the femtosecond laser could be applied to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…Compared to other organic compounds studied via NPLIN in the same experimental setup, the crystalline growth speed of the cocrystal is so far lower. For glycine, 15 carbamazepine, 29 and sulfathiazole, 34 the induction time is between 10 and 30 min and filtered after only 3 h, while the MZL limit varies from 1.5 to 7 days for glycine, 15 3 days for carbamazepine, 31 and 7 days for sulfathiazole. 34 In these three cases, MZL is lower than those observed with CAF-GAL cocrystals, crystallization kinetics is slower by a factor 10, and the size of the cocrystal is very small.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to other organic compounds studied via NPLIN in the same experimental setup, the crystalline growth speed of the cocrystal is so far lower. For glycine, 15 carbamazepine, 29 and sulfathiazole, 34 the induction time is between 10 and 30 min and filtered after only 3 h, while the MZL limit varies from 1.5 to 7 days for glycine, 15 3 days for carbamazepine, 31 and 7 days for sulfathiazole. 34 In these three cases, MZL is lower than those observed with CAF-GAL cocrystals, crystallization kinetics is slower by a factor 10, and the size of the cocrystal is very small.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Cocrystals present different physicochemical properties than the pure API: solubility in water may be increased, stability can be enhanced, susceptibility to moisture can be reduced, and so forth. 28 Several APIs have been crystallized via NPLIN: L-histidine, 29 acetaminophen, 30 carbamazepine, 31 indomethacin, 32 sulfathiazole, 33,34 and aspirin. 35 However, no nucleation via NPLIN has been tried in the specific case of the cocrystals.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it was observed that the length of the crystals decreased with an increase in the double pulse delay time. Finally, it was reported that the aspect ratio distribution Yu et al 97 demonstrated polymorph control of sulfathiazole in a mixture of water and ethanol supersaturated solution by focusing femtosecond laser light (800 nm) through a 5x objective for a period of 1 minute, 500 µm from the air-liquid interface, as shown in Figure 16i. In other experiments, the laser source was combined with ultrasound, using a 40 kHz, 50 W ultrasonic cleaning machine to check the influence of ultrasound exposure along with laserinduced nucleation.…”
Section: Potential For Controlling Polymorphic Formmentioning
confidence: 99%
“…[14][15][16] Traditional thermodynamic and kinetic methods cannot achieve efficient polymorph separation. 17,18 Various external auxiliary methods such as supercritical CO 2 , 19 laser induction, 20,21 polymer induction, 22,23 self-assembled monolayers (SAMs), 24 gel phase crystallization, 25,26 etc. were applied to control the concomitant polymorphism.…”
Section: Introductionmentioning
confidence: 99%